2019
DOI: 10.1016/j.molcel.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Processing of Displacement Loops during Recombinational DNA Repair

Abstract: Highlights d Development of a physical assay for D-loop detection in cells d Srs2, Mph1, and Sgs1-Top3-Rmi1 (STR) regulate D-loop levels in vivo d Two distinct pathways (Srs2 and Mph1, STR) target different D-loop species d Rdh54 delineates the two D-loop reversal pathways

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(131 citation statements)
references
References 77 publications
(152 reference statements)
11
120
0
Order By: Relevance
“…This study also led to the conclusion that, in addition to D-loops, Sgs1, and Srs2, but not Mph1, also disassemble HJ-containing intermediates [59]. In vitro assays of D-loop reconstitution showed that Mph1 is extremely efficient in displacing these structures [60], a feature that supports a role for the helicase in promoting SDSA in vivo [13,61]. This Mph1-dependent bias to SDSA is fundamental to avoid the processing of recombination intermediates by nucleases that can contribute to the generation of COs (Figure 1).…”
Section: The Mph1 Helicase Contributes To D-loop Dismantlingmentioning
confidence: 72%
See 2 more Smart Citations
“…This study also led to the conclusion that, in addition to D-loops, Sgs1, and Srs2, but not Mph1, also disassemble HJ-containing intermediates [59]. In vitro assays of D-loop reconstitution showed that Mph1 is extremely efficient in displacing these structures [60], a feature that supports a role for the helicase in promoting SDSA in vivo [13,61]. This Mph1-dependent bias to SDSA is fundamental to avoid the processing of recombination intermediates by nucleases that can contribute to the generation of COs (Figure 1).…”
Section: The Mph1 Helicase Contributes To D-loop Dismantlingmentioning
confidence: 72%
“…Notably, Sgs1 is dispensable for full-length meiotic DSB resection, which mainly relies on Exo1 and Tel1 activities [75]. On the other hand, the STR complex, via Top3 decatenation activity, is capable of dismantling D-loops in vivo, favoring the formation of NCOs by the SDSA repair pathway both in the meiotic [76,77] and mitotic [13] programs ( Figure 1). Although in vitro assays using artificial D-loops suggested that Top3 preferentially dismantles protein-free D-loops [78,79], more recent single-molecule imaging analysis has revealed that Sgs1 possesses the ability to disrupt Rad51-bound ssDNA nucleofilaments [80].…”
Section: The Dissolvase Role Of the Multifaceted Str Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Rdh54 is important for HR in diploid cells, but roles in haploid cells are also emerging. Notably, the recently identified role for Rdh54 in regulating D-loop formation [174], and thereby HR levels, could become increasingly important in the absence of Rrm3 when greater numbers of HR substrates are likely to form at replication pause sites. That Sgs1-Top3-Rmi1 and Srs2 define two independent pathways of D-loop reversal could contribute to the synthetic lethality of the rrm3∆ mutation with sgs1∆ and srs2∆ mutations as well as its suppression by RAD51 deletion [62,83,173,174].…”
Section: Cellular Response To Replication Fork Stalling In the Absencmentioning
confidence: 99%
“…Notably, the recently identified role for Rdh54 in regulating D-loop formation [174], and thereby HR levels, could become increasingly important in the absence of Rrm3 when greater numbers of HR substrates are likely to form at replication pause sites. That Sgs1-Top3-Rmi1 and Srs2 define two independent pathways of D-loop reversal could contribute to the synthetic lethality of the rrm3∆ mutation with sgs1∆ and srs2∆ mutations as well as its suppression by RAD51 deletion [62,83,173,174]. Upregulation of Mph1, which also functions in D-loop disassembly [175], was also observed in the rrm3∆ mutant, albeit to a lesser extent than Top2, Rdh54 and Rad5, and further supports the increased requirement for tight regulation of D-loop formation in the absence of Rrm3 [19,175].…”
Section: Cellular Response To Replication Fork Stalling In the Absencmentioning
confidence: 99%